Analisis Satire Dalam Konten Tiktok @Kelvinsteviano1 - Debrina Putri Fauzi; Dianita Indrawati (Jurnal Ilmu Bahasa, Sastra, dan Budaya, 2026)
This research is motivated by the development of social media, particularly TikTok, which is not only used as a means of entertainment, but also as a medium for conveying social criticism through the use of satire. Satirical content on social media is growing rapidly because it is able to highlight social phenomena in a light, humorous, and close to people's lives, especially the younger generation. Through this phenomenon, this study aims to describe the types of satire, the meaning of satire, and the function of satire in Kelvin Steviano's TikTok content. This study uses a descriptive qualitative approach. The research data source is speech containing satire in the TikTok video content of the account @kelvinsteviano1. Data was collected using the listening method with the Listening Free Involvement Conversation (SBLC) technique and note-taking technique. Furthermore, the data were analyzed using the referential matching method with the Determining Elements (PUP) technique and the distribution method with the Direct Elements Sharing (BUL) technique. The results found in this study are that there are  three types of satire in 44 data consisting of 7 Horatian satire, 9 Juvenalian satire, and 28 Menippean satire. In addition, three intentions of satire were found in TikTok @kelvinsteviano1, namely satirizing and laughing at 9 data, satirizing and criticizing 27 data, and satirizing and raising awareness 5 data. Then also found three functions of satire which include 4 data entertainment function, 34 data social criticism function, and 6 data satire function as a lesson.